MEANING CONSTRUCTION IN INDIGENOUS PEOPLES juridical Article 18B of the Constitution NRI YEAR 1945 FOR IDENTIFICATION OF RECHT GEMENSHAPEN - Sabardi, Lalu (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The purpose of this research as stated in Article 18B Constitution of Republic Indonesia 19454) that âThe State recognizes and respects traditional communities along with their traditional customary rights as long as these remain in existence and are in accordance with the societal development and the principles of the Unitary State of the Republic of Indonesia, and shall be regulated by law.â to be reality. This research to be importance for it related to the principle of Adat Law Community as the organization unit of Indonesian indigenous people which practically want to be found the certainty of legal protection that must be given by the State as unit of highest legal association